CRAFTING NEW MEANING: INNOVATION AND EXPLORATION OF MATERIALS AMONG GUJARAT’S APPLIQUÉ CRAFT CLUSTERS - Pramanick, Suvankar; Ghorui, Debasish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Indian context, textile material and techniques of clothing has evolved throughout ages, contributing to the reflection of human identity and cultural values. Concurrently, owing to the dynamic nature of the materials and changing market demand, some of the traditional craftsmanship have significantly redefined textile material’s interconnectedness with human society. In due process, the craftsmen have incorporated innovative design strategies to survive within a competitive market, where material and humans have engaged in non-verbal communication to generate meaningful representations of both within the given socioeconomic structure. The craft cluster of Chauhan family in Gujarat is one such instance, who have introduced significant transformation to the traditional practice of appliqué to sustain and evolve within the changing market demand. This study explores contemporary challenges faced by this industry, along with the artisans involved, to evaluate the design solutions, strategic survival mechanism, and product evolution of the same, while preserving traditional ethos.